(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
In the history of Venezuela there are many characters whose performance is unknown, despite the important contributions made during his life in favor of society. Aquilino Juares, from Cabudare, is one of these characters of the 19th century, who from the military field, and especially from the civilian; contributed to the enlargement and progress of the Lara state. From the position of President of this state (18941898), he carried out an outstanding work in support of the educational and cultural field, which we intend to address in this work.